Methodology issues in islamic finance : the "Black Swan" and the zann perspectives - Rafikov, Ildus
The study explores the issues of methodology in Islamic finance from the perspectives of unforeseen random events, called “Black Swan,” and weak conjecture, referred to as zann. The thesis asserts that the methodology of modern Islamic finance, being a part of the conventional financial system, suffers from weak conjecture and, therefore, it puts the achievements and future development of the industry in danger of crises. Muslim economists and some industry professionals for decades have been warning about this inherent weakness of the present system, which this study confirms and highlights some issues within the methodological framework employed by many researchers and practitioners to advance the Islamic finance industry. The study employs a qualitative research of the discourse, analysing literature on methodology of economics and finance from the conventional and Islamic perspectives, reviews the present state of the financial industry, both conventional and Islamic, their weaknesses and reasons behind crises that have been plaguing the financial system with increasing frequency, and argues that if the Islamic finance industry continues to follow in the footsteps of the conventional finance, it may soon face “Black Swan” type negative large-scale events. Consequently, an alternative methodology based on a multidisciplinary approach is proposed. It promotes a collaborative framework for research and development based on existing methodologies of the Shari'ah and social sciences with the aid of guiding principles, designed to offer simpler, scalable, and sustainable solutions. The methodology was verified by a panel of experts in finance, Shari'ah, economics, law and business. Their reviews and analyses are then incorporated into a modified methodology, which argues for greater collaboration between various stakeholders, including experts in natural sciences and ICT, while the guiding principles are more precise. Hence, it is argued that by following the collaborative multidisciplinary methodology, Islamic finance can avoid large-scale “Black Swan” events, strengthen the real economy and enhance its position in the financial milieu.